2014
DOI: 10.1007/s00540-014-1960-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of clinical experience of the Macintosh laryngoscope on performance with the Pentax-AWS Airway Scope®, a rigid video-laryngoscope, by paramedics in Japan

Abstract: We found that paramedics could achieve a high tracheal intubation success rate using the AWS independent of previous airway management experience. Better intubation performance with the AWS was observed in paramedics without clinical experience with the ML.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…One study, however, has shown that, compared with novice paramedics who had no experience with the use of a Macintosh laryngoscope, those with previous training of tracheal intubation using a Macintosh laryngoscope had a lower success rate of tracheal intubation using a videolaryngoscope [29]. This report indicates that training with a videolaryngoscope is necessary, and we need to find an appropriate training method [30].…”
Section: Adequate Planningmentioning
confidence: 86%
“…One study, however, has shown that, compared with novice paramedics who had no experience with the use of a Macintosh laryngoscope, those with previous training of tracheal intubation using a Macintosh laryngoscope had a lower success rate of tracheal intubation using a videolaryngoscope [29]. This report indicates that training with a videolaryngoscope is necessary, and we need to find an appropriate training method [30].…”
Section: Adequate Planningmentioning
confidence: 86%
“…Since 2011, ELSTs have also been allowed to use rigid video laryngoscopes after completion of additional training. 30 ELSTs in Japan are not permitted to perform ETI except in patients with OHCA. The indications for ETI in patients with OHCA 31 include: (1) impossibility of maintaining ventilation without ETI, such as foreign-body airway obstruction, and (2) cases in which the medical control doctor judges ETI to be required.…”
Section: Methodsmentioning
confidence: 99%
“…Ota et al [3] performed an observational study comparing the success rate of tracheal intubation using a video laryngoscope (Pentax Airway Scope) by paramedics with and without previous training of tracheal intubation using a Macintosh laryngoscope in anesthetized patients. The success rate of tracheal intubation using the Airway Scope was high for both groups of paramedics, indicating the usefulness of the video laryngoscope.…”
Section: Main Findings Of the Studies Of Ota And Colleaguesmentioning
confidence: 99%
“…In contrast, for the video laryngoscopes, this alignment is not required to see the glottis, and thus successful rate of tracheal intubation is generally high even in patients with restricted head and neck positions [7,8]. With these advantages in mind, Ota et al [3] have concluded that previous experience with a Macintosh laryngoscope is not necessary or required for paramedics to be trained to use the Airway Scope effectively.…”
Section: Advantages Of Video Laryngoscopesmentioning
confidence: 99%
See 1 more Smart Citation